Prioritas Pengembangan Kredit Union Mototabian dengan Metode AHP dan Fuzzy - AHP - Jozef Raco (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
The credit union is a non-bank financial institution that plays a very important role in helping to meet the needs of the community. Several previous studies have emphasized the economic aspect and its contribution. This study aims to examine the priority factors for the development of the Mototabian Credit Union in North Sulawesi using the Analytical Hierarchy Process and Fuzzy AHP. The results show that in terms of criteria, human resources factors must be the main concern. The main priority that must be considered in the development of this Credit Union is member loyalty and service spirit. This study states the strategic aspects of the development of the Mototabion Credit Union with a quantitative approach that focuses on its members